Unmasking the Hidden Hero: Strengthening North Sumatra’s Iconic Commodities through Financial Services - Sitohang, Gresia Septina; Oktania, Ainur; Manihuruk, Frido Evindey (Jurnal Inovasi Ekonomi, 2025)
This study reveals the fascinating story behind North Sumatra's iconic commodities and how the financial services sector can act as a hidden hero to strengthen their development. Through multiple regression analysis on rubber, arabica coffee, and palm oil production data as well as the 2010-2023 agricultural sector GRDP obtained from the North Sumatra Central Bureau of Statistics, it was found that arabica coffee and rubber significantly boosted regional economic growth, while the potential of palm oil has not been maximized. Like a masked hero, the financial services sector, which includes banks, micro institutions, and fintech, has the ability to provide “superpowers” for North Sumatra's leading commodities. By providing effective access to finance, they can help improve the productivity, quality, and competitiveness of these iconic products. This research proposes smart policy recommendations to strengthen the synergy between the financial services sector and commodity development, bringing North Sumatra towards more inclusive and sustainable economic growth.